(untitled) - Gardner, Bryan (Oxford, 2000)
This is an accessible guide to using English in the classroom for non-native speaker teachers. The book is in two parts: Section 1 provides advice on issues, such as how to check that learners have understood and when to use English. Section 2 looks at different situations in the classroom, for example, 'Using the coursebook' and 'Giving instructions
Keywords: English language; Textbooks for foreign speakers